The Civil Servants’ Professional Mobility Structure - Shpektorenko, Igor V. (LRIPA NAPA, 2009)
Considerable development of the country’s governance can’t be achieved only through improvement of legal and regulatory basis or allocating great funds to material and technical development of civil service and government machinery in general. We believe that, the main objective in this direction is to achieve perfect performance and professionalization of civil servants. In our opinion, it can be implemented through combining interests in the civil servants’ professional growth of the both sides – a civil servant and the country. Thus, personality focused approach to a civil servant’s career planning and development should be combined with the mission and objectives of the government bodies.
Keywords: Professional Mobility; civil servant; adaptation activity; occupational satisfaction